Impact of clinical simulation on the comprehensive development of competencies in medical students - Briones Morales, Victor Euclides (2024)
Introduction: Medical education seeks more than theoretical instruction; it pursues to develop practical and cognitive competencies through clinical simulation strategies, a tool that replicates complex and safe environments, fostering technical and soft skills; however, its global and Latin American adoption faces resource and training limitations. Objective: To evaluate the relationship between the implementation of clinical simulation strategies and the development of professional competencies, based on the perception of medical students in an Ecuadorian university. Methods: A positivist paradigm study was conducted, with a quantitative approach, non-experimental, descriptiveinferential, cross-sectional design, involving 93 eighth and ninth semester students, through the application of surveys with Likert-type scales to measure the perception of simulation (V1) and the development of competencies (V2). The data were processed in Excel and SPSS 25, using Spearman's correlation test to evaluate the relationship between the two study variables. Results: 60% of the students considered the simulation as an effective strategy for learning; however, 34% showed average evaluations. Debriefing was positively evaluated by 66% of the participants, highlighting its relevance in the consolidation of learning. Spearman's correlation showed a moderate-high positive relationship (Rho=0.641, p<0.01) between simulation and competency development, suggesting that its improvement impacts favorably on student skills. Conclusions: The findings confirm the effectiveness of clinical simulation in improving medical competencies, such as decision-making and teamwork, which coincides with previous work. However, there is evidence of problems to be solved, such as improvements in infrastructure and teacher training to maximize its impact on medical education.